The Influence of Marketing Communication Via Instagram at the Al Amjad Islamic School in Medan on the Perceptions and Educational Preferences of Students' Parents - Muhammad Hafiz Pulungan; Suwardi Lubis; Syukur Kholil (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to analyze the influence of marketing communication of Al Amjad Islamic School through Instagram on the perception and educational preferences of students' parents. The study used a quantitative approach with a correlation method. The sampling technique used stratified random sampling with 325 student samples at Al Amjad Islamic School Medan. The results showed that the advertising dimension obtained a value of 88%, the facility dimension obtained a value of 87.1% and the peer dimension obtained a value of 87.7%. The results of simultaneous calculations showed that the H0 hypothesis was rejected and Ha was accepted so that simultaneous marketing communication had a significant effect on educational perceptions and preferences